2019
DOI: 10.1038/s41467-019-12137-1
|View full text |Cite
|
Sign up to set email alerts
|

A potent broadly neutralizing human RSV antibody targets conserved site IV of the fusion glycoprotein

Abstract: Respiratory syncytial virus (RSV) infection is the leading cause of hospitalization and infant mortality under six months of age worldwide; therefore, the prevention of RSV infection in all infants represents a significant unmet medical need. Here we report the isolation of a potent and broadly neutralizing RSV monoclonal antibody derived from a human memory B-cell. This antibody, RB1, is equipotent on RSV A and B subtypes, potently neutralizes a diverse panel of clinical isolates in vitro and demonstrates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…Unfortunately, nearly all such efforts to develop mAb as therapy for ARIs have been met with disappointing results. Some human or humanized mAbs developed as antivirals that have advanced past Phase 1 studies include MEDI-8852 (influenza; IC 50 ~ 41–4050 ng/mL; 750 or 3000 mg) [ 155 , 156 ], MHAA4549 (influenza; IC 50 ~ 195–6765 ng/mL; 3600 or 8400 mg) [ 44 , 157 ], CR8020 (influenza; IC 50 ~ 9–500 ng/mL; 30 mg/kg) [ 158 ], CT-P27 (influenza; IC 50 ~ 15 μg/mL; 10–20 mg/kg) [ 136 ], diridavumab (influenza; IC 50 ~ 18–2200 ng/mL; 30 mg/kg) [ 159 , 160 ], VIS-410 (influenza; IC 50 ~ 30–7000 ng/mL; 2000 or 4000 mg) [ 161 , 162 ], Motavizumab (RSV; IC 50 ~ 20 ng/mL; 15 mg/kg [ 163 ]), and palivizumab (RSV; IC 50 ~ 163–360 ng/mL; 15 mg/kg) [ [163] , [164] , [165] ]. None of these mAbs were noted to have major safety concerns, which supports the anticipated safe use of mAbs against SARS-CoV-2.…”
Section: Clinical Efficacy Of Mabs For the Treatment Or Prevention Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, nearly all such efforts to develop mAb as therapy for ARIs have been met with disappointing results. Some human or humanized mAbs developed as antivirals that have advanced past Phase 1 studies include MEDI-8852 (influenza; IC 50 ~ 41–4050 ng/mL; 750 or 3000 mg) [ 155 , 156 ], MHAA4549 (influenza; IC 50 ~ 195–6765 ng/mL; 3600 or 8400 mg) [ 44 , 157 ], CR8020 (influenza; IC 50 ~ 9–500 ng/mL; 30 mg/kg) [ 158 ], CT-P27 (influenza; IC 50 ~ 15 μg/mL; 10–20 mg/kg) [ 136 ], diridavumab (influenza; IC 50 ~ 18–2200 ng/mL; 30 mg/kg) [ 159 , 160 ], VIS-410 (influenza; IC 50 ~ 30–7000 ng/mL; 2000 or 4000 mg) [ 161 , 162 ], Motavizumab (RSV; IC 50 ~ 20 ng/mL; 15 mg/kg [ 163 ]), and palivizumab (RSV; IC 50 ~ 163–360 ng/mL; 15 mg/kg) [ [163] , [164] , [165] ]. None of these mAbs were noted to have major safety concerns, which supports the anticipated safe use of mAbs against SARS-CoV-2.…”
Section: Clinical Efficacy Of Mabs For the Treatment Or Prevention Ofmentioning
confidence: 99%
“…Indeed, the majority of the current anti-SARS-COV-2 mAbs in active preclinical and clinical development have exceptional potencies (IC 50 values <10 ng/mL range) ( Table 1 ). These potencies substantially exceed nearly all of the antiviral mAbs that were previously advanced into clinical studies and failed, including palivizumab against RSV (Synagis; IC 50 ~ 163–360 ng/mL [ [163] , [164] , [165] ]), MEDI8852 against influenza (IC 50 ~ 41–4050 ng/mL [ 155 , 156 ]), and MHAA4549 against influenza (IC 50 ~ 195–6765 ng/mL [ 44 , 157 ]). Theoretically, assuming the concentrations of these anti-SARS-CoV-2 mAbs in BALF can reach ~0.1–0.2% of the mAb concentration in plasma, consistent with prior non-human primate studies, the local concentration should substantially exceed the IC 50 of these mAbs.…”
Section: Strategies To Overcome Past Failuresmentioning
confidence: 99%
“…The structure of the R4.C6 Fab-post-fusion RSV F complex obtained by cryo-EM showed that the antibody binds to a cross-protomer area in between site II and IV. Recently, a site IV human antibody, RB1, was co-crystallized in complex with pre-fusion RSV F, and a half-life extended variant of this antibody is in clinical development (74).…”
Section: Antigenic Epitopes On the Rsv F Proteinmentioning
confidence: 99%
“…108 , 109 In a similar endeavor to extend the half-life and reduce the number of injections required to protect infants during the RSV season, MK-1654, a broadly neutralizing human RSV antibody that targets the conserved site IV of the RSV F protein is being tested. 110 A double-blind, randomized, placebo controlled study is currently recruiting healthy pre-term and full-term infants to evaluate the safety, tolerability, pharmacokinetics, and incidence of anti-drug antibodies following a single dose of MK-1654. 111 Early studies show that the parent compound of MK-164, RB1 is approximately 50-fold more potent in vitro than palivizumab against both RSV A and B subtypes.…”
Section: Infant Rsv Immune Responsesmentioning
confidence: 99%